Infrared and raman spectra of nanoporous SiO2 matrix filled with BaTiO3 nanoparticles - Lopez J.A.R. (2020)
Nanocomposite in the form of a porous matrix SiO2 with average pore size of 320 nm filled with barium titanate nanoparticles in paraelectric cubic phase was obtained. Shift of the stretching vibration of Si-O-Si to higher frequencies caused by increased strengthening of the network in the matrices has been observed. Also demonstrated that decrease in the intensity of the absorption relating to Si-O(H) stretching vibration relative to Si-O(-Si) stretching vibration. Raman scattering spectra demonstrate the presence of both a cubic and a tetragonal ferroelectric crystalline phase in the filler nanoparticles. Thus, the mechanical deformation of nanoparticles in the pores of the matrix can lead to a change in the crystalline phase of the filler. © 2020 Trans Tech Publications Ltd, Switzerland.